2021
DOI: 10.1177/23094990211021536
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo biomechanical evaluations of suture anchors for repairing grade 3 superficial medial collateral ligament injury in a porcine model

Abstract: Purpose: To clarify the biomechanical and radiological outcomes of superficial medial collateral ligament (sMCL) repair using suture anchors in a large animal model. Methods: The right sMCLs of nine male castrated pigs was completely detached at the femoral attachment. sMCL repair surgery was performed using two suture anchors. The same skin incision, sMCL exposure, and immediate wound closure were made at the left knee as a sham surgery. Magnetic resonance imaging was performed preoperatively and 4 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…8,19,21 Clinical studies comparing onlay and intraosseus screw fixation are missing, but a recent animal study examined the biological properties of an onlay MCL fixation, which demonstrated nonsignificant differences when compared with the native MCL. 35 These results are in line with clinical data showing good to excellent results of ligament fixation using the anchor technique. 19,21 Another technical benefit of the aLET is the minimized risk of tunnel interference when performing a concomitant ACLR.…”
Section: Discussionsupporting
confidence: 85%
“…8,19,21 Clinical studies comparing onlay and intraosseus screw fixation are missing, but a recent animal study examined the biological properties of an onlay MCL fixation, which demonstrated nonsignificant differences when compared with the native MCL. 35 These results are in line with clinical data showing good to excellent results of ligament fixation using the anchor technique. 19,21 Another technical benefit of the aLET is the minimized risk of tunnel interference when performing a concomitant ACLR.…”
Section: Discussionsupporting
confidence: 85%
“…The present large-animal study showed that dynamic stiffness, measured using Myoton PRO, exhibited a moderate correlation with length change, measured using biomechanical machines, at both AT0 and AT2, consistent with the findings of the human AT study [ 15 ]. Biomechanical testing using tensile testing machines on porcine anterior cruciate and medial collateral ligaments has been reported [ 19 - 20 ]. Significant length changes, as observed with the long-axis method, indicate greater translation of the tissue and softer tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Sutures were then placed proximal to the AT. The calcaneus was inserted into aluminum tubes with cement [ 19 - 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 scalpel to create an avulsion injury ( Fig 1 B). 9 , 13 sMCL repair was performed using 2.0 nylon thread ( Fig 1 C) intended only to reduce the detached sMCL to its anatomic position, followed by UHMWPE tape augmentation by loading suture augmentation (ULTRATAPE; Smith & Nephew Endoscopy, Andover, MA) and 2 interference screws (Cannu-Flex SILK; Smith & Nephew Endoscopy). The initial tension of 30 N was applied to the suture augmentation, and sutures from the femoral sMCL anchor were secured to the anatomic tibial insertion of the MCL ( Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%